ExtraUterine Growth Restriction (EUGR) in Preterm Infants: Growth Patterns, Nutrition, and Epigenetic Markers. A Pilot Study - Tozzi, Maria Giulia; Moscuzza, Francesca; Michelucci, Angela; Lorenzoni, Francesca; Cosini, Cinzia; Ciantelli, Massimiliano; Ghirri, Paolo (Frontiers in Pediatrics, 2018)
Background/Aims. IntraUterine (IUGR) and ExtraUterine Growth Restriction (EUGR) may induce reprogramming mechanisms, finalized to survive before and after birth. Nutritional factors and other environmental signals could regulate gene expression through epigenetic modification, but the molecular mechanisms involved are not yet well understood. Epigenetic mechanisms could be considered as a bridge between environmental stimuli and long lasting phenotype, acquired during the intrauterine life and the first weeks of life. Our aim was to investigate the relationship between growth patterns, nutritional determinants and epigenetic pathways. Methods. We enrolled 38 newborns admitted to Neonatal Intensive Care Unit (NICU) at University Hospital of Pisa. Gestational age at birth was <34 weeks and post-menstrual age (PMA) was 36-42 weeks at discharge. We excluded infants with malformations or clinical syndromes. EUGR was defined as the reduction in weight z score between birth and discharge >1SD. We also evaluated DNA methylation of Imprinting Centre 1 (IC1) at birth and at discharge. Results. We observed a decrease in SD of weight and head circumference mainly during the first weeks of life. We found a correlation between EUGR for weight and for head circumference and an increased IC1 methylation (p=0.018 and p=0.0028 respectively). We observed a relationship between reduced protein and lipid intake and IC1 hypermethylation (p=0.009 and p=0.043 respectively). Conclusion. IC1 hypermethylation could be a reprogramming mechanism to promote a catch-up growth, by means of an increased Insulin-like growth factor 2 (IGF2) expression, that may have potential effects on metabolic homeostasis later in life.